Upaya Peningkatan Keterampilan dan Kesejahteraan Keluarga melalui Pelatihan Kokedama di Desa Gentungan, Kabupaten Karanganyar - Bunga Widarizki, Restik; Nuzul Isnaini Fathurrahmah; Rohima Tazkiyah Rosyida; Purwaningsih; Novia Tri Utami; Nuri Luthfi Asih; Nabila Shofiatuz Zahroh; Mardiani Rahayu Pramesti; Danang Purwanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to determine efforts to improve skills and family welfare through training in Gentungan Village, Mojogedang District, Karanganyar Regency. Kokedama skill is a technique for planting ornamental plants using coconut fiber originating from Japan. This kokedama technique can be done by many people because of the use of materials that are easily available. Gentungan Village has its own charm with abundant natural resources. This kokedama skills training aims as one of the community empowerment efforts in utilizing local potential. This program is held using the community empowerment method, starting from field surveys, program preparation, coordination with stakeholders, program implementation, and evaluation. The implementation of kokedama training held at the Farmhouse with resource persons was enthusiastically received by local residents. The results showed that increased creativity and skills have opened up new business opportunities for the people of Gentungan Village. In addition, this kokedama training can be one of the efforts in developing and empowering local tourism potential as well as preserving the environment.